2018
DOI: 10.1002/smll.201704073
|View full text |Cite
|
Sign up to set email alerts
|

NiO as a Bifunctional Promoter for RuO2 toward Superior Overall Water Splitting

Abstract: Conventional development of nanomaterials for efficient electrocatalysis is largely based on performance-oriented trial-and-error/iterative approaches, while a rational design approach at the atomic/molecular level is yet to be found. Here, inspired by a fundamental understanding of the mechanism for both oxygen and hydrogen evolution half reactions (OER/HER), a unique strategy is presented to engineer RuO for superior alkaline water electrolysis through coupling with NiO as an efficient bifunctional promoter.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
180
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(195 citation statements)
references
References 53 publications
4
180
0
1
Order By: Relevance
“…Rapidly increasing international development of renewable and green energy sources has drawn widespread attention of researchers to water‐splitting oxygen and hydrogen production via the electrochemical oxygen evolution reaction (OER) and hydrogen evolution reaction (HER), respectively . To enhance these reactions to commercially viable rates, however, high‐performance electrocatalysts are required to overcome the activation energies associated with OER and HER .…”
Section: Introductionmentioning
confidence: 99%
“…Rapidly increasing international development of renewable and green energy sources has drawn widespread attention of researchers to water‐splitting oxygen and hydrogen production via the electrochemical oxygen evolution reaction (OER) and hydrogen evolution reaction (HER), respectively . To enhance these reactions to commercially viable rates, however, high‐performance electrocatalysts are required to overcome the activation energies associated with OER and HER .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Ruthenium, owing to the advantages of the cheapest among platinum group metals and excellent performance in many applications such as N 2 electrochemical reduction and selective hydrogenation, has attracted much attention. [17][18][19][20] Forinstance, Su and co-workers have obtained Cu-doped RuO 2 hollow porous polyhedra through one-step annealing of Ru-exchanged Cu-BTC derivatives,w hich showed remarkable OER performance in 0.5 m H 2 SO 4 . [17][18][19][20] Forinstance, Su and co-workers have obtained Cu-doped RuO 2 hollow porous polyhedra through one-step annealing of Ru-exchanged Cu-BTC derivatives,w hich showed remarkable OER performance in 0.5 m H 2 SO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] Significantly,i th as also been shown that Ru-based electrocatalysts are active in both HER and OER. [17][18][19][20] Forinstance, Su and co-workers have obtained Cu-doped RuO 2 hollow porous polyhedra through one-step annealing of Ru-exchanged Cu-BTC derivatives,w hich showed remarkable OER performance in 0.5 m H 2 SO 4 . [21] Liu and colleagues have synthesized multi-heterogeneous Ni@Ni 2 P-Ru nanorods showing excellent electrocatalytic HER performance.…”
Section: Introductionmentioning
confidence: 99%
“…As the energy crisis becomes more and more prominent because of the rapidly growing energy demand, the design of efficient and cost‐effective catalysts for electrochemical energy conversions to meet the high demands of renewable energies becomes highly urgent . The oxygen evolution reaction (OER, 4 OH − → 2 H 2 O + O 2 + 4 e − in base) is the vital step for many renewable‐energy technologies . However, the kinetics of OER is sluggish due to the multistep proton‐coupled electron transfer, which requires large overpotential to reach desirable current density .…”
Section: Figurementioning
confidence: 99%